Structural change and gender sectoral segregation in sub-Saharan Africa - Zuazu, Izaskun (Levy Economics Institute, 2023)
Structural change has long been at the core of economic development debates. However, the gender implications of structural change are still largely unexplored. This paper helps to fill this gap by analyzing the role of structural change in the gender distribution of sectoral employment in sub-Saharan African countries. I employ aggregate and disaggregate measures of gender sectoral segregation in employment on a panel database consisting of 10 sectors and 11 countries during 1960-2010. Fixed effects and instrumental variables' regression models show a significant, non-linear link between labor productivity and gender segregation. Increasing labor productivity depresses gender segregation at initial phases of structural change. However, further productivity gains beyond a certain threshold of sectoral development increases gender segregation. Country-industry panel data models complement the analysis by considering relative labor productivity as a determinant of sectoral feminization. The estimates suggest that manufacturing, utilities, construction, business, and government services are key to correcting gender biases in employment along the process of structural change.
10419/283218
Keywords: Graue Literatur; structural change; gender sectoral segregation; dissimilarity index; association index; instrumental variables